PRESENTATION, ANALYSIS AND VALIDATION OF A RESEARCH INSTRUMENT TO SURVEY THE HABITS OF USE OF DERMOCOSMETICS - de Proença, Camille Schmidt; Nobre, Leandra Marques Ferreira; Schmidt, Carla Adriana Pizarro (Seven Editora, 2025)
The objective of the present study was to present a reliable instrument for conducting survey-type research on the knowledge, use and habits of the interviewees in relation to dermocosmetics, consultations with dermatologists and the interviewees' concepts about the necessary skin care. To this end, a questionnaire was prepared, approved by the research ethics committee and applied to 199 people, so that the necessary statistical reliability tests could be carried out with the results. The results obtained showed that the questionnaire elaborated can be considered reliable and thus the present study presents this new research tool, as no questionnaire for this purpose was found ready and validated in the recent literature that was researched. It should be noted that it is very important to know people's behaviors, attitudes, opinions and preferences so that you can act consciously in the dermatology market, seeking actions that can improve people's quality of life, prevent diseases and make the population aware of the behaviors that must be modified or maintained in certain situations, because knowing the opinions and behavior of the client is essential in any area of activity.DOI: https://doi.org/10.56238/sevened2024.037-190